Kriptografi Homomorfik dalam Anonimisasi Data untuk Pengolahan Data pada Sistem E-Voting - Muhammad Naufal Zhafran Soleh (Jurnal Masyarakat Informatika, 2024)
In today's age of technological advancement, protecting data security and privacy is a significant challenge. This study seeks to prove the effectiveness of Homomorphic Cryptography techniques, which allow data to be processed while remaining encrypted, addressing the limitations of standard encryption methods that only secure data but do not enable processing of encrypted information. The research approach involves analyzing Homomorphic Cryptography by designing an e-voting system that utilizes the Paillier algorithm, enabling the processing of vote data while it is encrypted, along with generating keys for encrypting and decrypting the votes. The results of this study indicate that implementing Homomorphic Cryptography within a web-based e-voting platform successfully facilitates data processing in an encrypted state. Additionally, security testing via a Ciphertext-only attack did not reveal any plaintext information, while performance testing recorded an encryption-decryption time of 0.010 seconds. Shannon entropy analysis also yielded a result of 3.20 bits for a single encrypted vote.